Increasing Superoxide Production and the Labile Iron Pool in Tumor Cells may Sensitize Them to Extracellular Ascorbate - McCarty, Mark Frederick; Contreras, Francisco (Frontiers in Oncology, 2014)
Low millimolar concencentrations of ascorbate are capable of inflicting lethal damage on a high proportion of cancer cells lines, yet leave non-transformed cell lines unscathed; extracellular generation of hydrogen peroxide, reflecting reduction of molecular oxygen by ascorbate, has been shown to mediate this effect. Although some cancer cell lines express low catalase activity, this cannot fully explain the selective sensitivity of cancer cells to hydrogen peroxide. Ranzato and colleagues have presented evidence for a plausible new explanation of this sensitivity - a high proportion of cancers, via NADPH oxidase complexes or dysfunctional mitochondria, produce elevated amounts of superoxide. This superoxide, via a transition metal-catalyzed transfer of an electron to the hydrogen peroxide produced by ascorbate, can generate deadly hydroxyl radical (Haber-Weiss reaction). It thus can be predicted that concurrent measures which somewhat selectively boost superoxide production in cancers will enhance their sensitivity to i.v. ascorbate therapy. One way to achieve this is to increase the provision of substrate to cancer mitochondria. Measures which inhibit the constitutive hypoxia-inducible factor-1 (HIF-1) activity in cancers (such as salsalate and mTORC1 inhibitors, or an improvement of tumor oxygenation), or that inhibit the HIF-1-inducible pyruvate dehydrogenase kinase (such as dichloroacetate), can be expected to increase pyruvate oxidation. A ketogenic diet should provide more lipid substrate for tumor mitochondria. The cancer-killing activity of 42°C hyperthermia is to some degree contingent on an increase in oxidative stress, likely of mitochondrial origin; reports that hydrogen peroxide synergizes with hyperthermia in killing cancer cells suggest that hyperthermia and i.v. ascorbate could potentiate each other’s efficacy. A concurrent enhancement of tumor oxygenation might improve results by decreasing HIF-1 activity while increasing the interaction